Oral sucrose for pain control in nonneonate infants during minor painful procedures. Issue 5 (24th September 2012) - McCall, Jamie Michelle; DeCristofaro, Claire; Elliott, Lydia
Abstract Purpose To provide information regarding the effective use of oral sucrose as an analgesic for immunization and venipuncture procedures in the older infant. Data sources: Evidence‐based literature including original clinical trials, reviews, and clinical practice guidelines. Conclusions Most infants are exposed to multiple minor painful procedures during the first year of life. Oral sucrose solution in a 24% concentration at a dose of 2 mL approximately 2 min prior to the painful procedure has been shown effective in reducing pain during immunizations and venipuncture in the outpatient setting in infants aged 1–12 months old. Implications for practice Oral sucrose solution should be used as a pain reduction intervention in infants up to 12 months of age undergoing minor painful procedures. Its proven effectiveness as an analgesic, low rate of minor adverse events, ease of administration, and excellent availability make sucrose a good choice for this purpose. Additional research is needed regarding dose response in different infant age groups, optimal concentration of sucrose solution, need for multiple sucrose dosing, adjustment for multiple painful procedures, and addition of optimal nonpharmacologic interventions as a combination approach.